FOTO IKLAN SEBAGAI MEDIA PROMOSI PADA INSTAGRAM "AH LURIK" - Achmad Syaeful Huda; Muhammad Fajar Apriyanto; Adya Arsita (Specta : Journal of Photography, Arts, and Media, 2022)
UMKM named "AH Lurik" is one of the lurik businesses located in Klaten City which has existed since 1959, has developed with a number of fashion products and accessories. The lack of promotion causes many young people, especially in terms of the products offered, therefore it is necessary to have visuals that are used to make young people interested in these products. Promotion is one means to boost sales, because promotions can attract the attention of consumers to buy. Promotion can be done by uploading photos through Instagram online media, the purpose of making this work is to make commercial photos as promotional media for "AH Lurik". The methods used include exploration, improvisation, and formation. In the exploration stage, they search for data, while improvisation performs experiments such as lighting, color selection, and objects, then in the formation of the work, they turn sketches into photographs. The basic form of work creation is a product variant, which is produced by “AH Lurik”, and is implemented through the social media platform Instagram. Thus, the results of commercial photography can attract the attention of consumers, especially young people to buy and preserve the lurik culture in Indonesia.